Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

3x-9 = 4x – 3 3x-9 = 4x – 3 3x-9 = 4x – 3 3x-9 = 4x – 3 3x-9 = 4x – 3 3x-9 = 4x – 3 3x-9 = 4x – 3 3x-9 = 4x – 3

3x-9 = 4x – 3
3x-9 = 4x – 3
3x-9 = 4x – 3
3x-9 = 4x – 3
3x-9 = 4x – 3
3x-9 = 4x – 3
3x-9 = 4x – 3
3x-9 = 4x – 3

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5964 Points
9 months ago
Dear Student

3x-9 = 4x – 3

3x – 4x = -3 + 9

-x = 6

x = – 6

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free